2017
DOI: 10.1210/en.2017-00437
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Alters the Lactating Mammary Gland and Nursing Behaviors in Mice Exposed During Pregnancy and Lactation

Abstract: High doses of estrogenic pharmaceuticals were once prescribed to women to halt lactation. Yet, the effects of low-level xenoestrogens on lactation remain poorly studied. We investigated the effects of bisphenol S (BPS), an estrogen receptor (ER) agonist, on the lactating mammary gland; the arcuate nucleus, a region of the hypothalamus important for neuroendocrine control of lactational behaviors; and nursing behavior in CD-1 mice. Female mice were exposed to vehicle, 2 or 200 µg BPS/kg/d from pregnancy day 9 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 74 publications
2
54
0
Order By: Relevance
“…In a 2017 article, mice were exposed to BPS during pregnancy and for the first 20 days of lactation. The mice showed normal mammary gland physiology at lactational day 2 (LD2), but at LD21, there was a significant decrease in the number of milk-producing lobules [18]. In the same year, another study was performed that included a study of the maternal behavior of mice after BPS exposure during pregnancy and lactation.…”
Section: Dietary Bps Exposure and Reproductionmentioning
confidence: 99%
“…In a 2017 article, mice were exposed to BPS during pregnancy and for the first 20 days of lactation. The mice showed normal mammary gland physiology at lactational day 2 (LD2), but at LD21, there was a significant decrease in the number of milk-producing lobules [18]. In the same year, another study was performed that included a study of the maternal behavior of mice after BPS exposure during pregnancy and lactation.…”
Section: Dietary Bps Exposure and Reproductionmentioning
confidence: 99%
“…Alonso‐Magdalena et al showed that BPA exposure during pregnancy in mice led to decreased insulin secretion, altered glucose tolerance and increased weight gain in the dam several months post‐partum indicating a predisposition to type 2 diabetes and obesity. In another model, La Plante et al showed that pregnant mice exposed to bisphenol S (an analogue of BPA) through postnatal day 20 showed that the mammary gland had less milk producing units along with altered nursing behaviour leading to stunted pup growth and development. These data have been confirmed in humans which showed that perfluorinated chemicals during pregnancy reduced the duration of breastfeeding .…”
Section: New Windows Of Exposurementioning
confidence: 99%
“…Translactational exposure, another way of indirect influence with environmental agents, is a reason of changes of male reproduction after lactating female mice were exposed to BPA [93]. Moreover, this type of exposure to bisphenols creates a risk of changed nursing behavior and also affects the mammary glands of mothers [94].…”
Section: Molecular Mechanism Of Eds In Extremely Low Dosesmentioning
confidence: 99%